THE EFFECT OF POLYPROPYLENE THICKNESS AND TEMPERATURE ON THE QUALITY OF CAYENNE PEPPER DURING STORAGE - Proklamita, Tri Luchi; Lende, Aloysius Ng. (International Journal of Research -GRANTHAALAYAH, 2020)
This study aims to determine the effect of different combinations of plastic thickness and temperature treatment combinations on the quality of cayenne pepper during storage, to determine the combination of plastic thickness and the right temperature to maintain the quality of cayenne pepper during storage. This study used a completely randomized design (CRD) with 9 treatments. The treatments tried in this study were thickness and temperature, namely Polypropylene 0.3 mm + tissue at 5°C, Polypropylene 0.3 mm + tissue at 10°C, Polypropylene 0.3 mm + tissue at 15°C, Polypropylene 0.4 mm + tissue at 5°C, Polypropylene 0.4 mm + tissue at 10°C, Polypropylene 0.4 mm + tissue at 15°C, Polypropylene 0.5 mm + tissue at 5°C, Polypropylene 0.5 mm + tissue at 10°C, Polypropylene 0.5 mm + tissue at 15°C. The treatment was repeated 3 times so that there were 27 experimental units. The results that showed the combination treatment of packaging thickness and temperature had a very significant effect on the storage quality of cayenne pepper on weight loss, vitamin C, texture, moisture content, and color, but had no significant effect on the color of the 8th day of the watershed. The combination treatment of plastic packaging thickness of 0.5 mm and temperature of 5°C can give the best effect on texture, vitamin C, moisture content, weight loss, and color, but at a thickness of 0.3 mm plastic and a temperature of 15°C does not give the best results on color 8th day.